2006
DOI: 10.2460/javma.229.7.1103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of epidural administration of morphine or morphine and bupivacaine for postoperative analgesia after premedication with an opioid analgesic and orthopedic surgery in dogs

Abstract: The preoperative epidurally administered morphine-bupivacaine combination induced better analgesia than morphine alone and should be considered for use in clinical patients. The degree of hemodynamic depression associated with the combination was considered acceptable for healthy patients undergoing elective surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 36 publications
7
68
1
4
Order By: Relevance
“…[5][6][7][8][9][10] Multimodal treatment, defined as the simultaneous use of different techniques or drugs, has been recommended because of its ability to act via various mechanisms, which results in additive or synergistic effects. [11][12][13] In 1 study, 14 investigators found that administration of a single drug is often not sufficient for controlling postoperative pain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] Multimodal treatment, defined as the simultaneous use of different techniques or drugs, has been recommended because of its ability to act via various mechanisms, which results in additive or synergistic effects. [11][12][13] In 1 study, 14 investigators found that administration of a single drug is often not sufficient for controlling postoperative pain.…”
mentioning
confidence: 99%
“…The combination of different techniques, such as administration of systemically active drugs (opioids, NSAIDs, and local anesthetics), use of regional analgesia (epidural and intra-articular analgesia), and physical methods (compression, cryotherapy, and immobilization), results in balanced analgesia and better pain control. 5,7,10,11,13 A combination of perioperative administration of NSAIDs, incisional and intra-articular analgesia, and postoperative cryotherapy has been successfully used for patients undergoing CrCL repair.…”
mentioning
confidence: 99%
“…Several studies have reported the high analgesic efficacy and long duration of action of ED morphine 2,5,19,20 . Nevertheless, a few published studies have described the analgesic properties and the efficacy of extradural tramadol in dogs 10,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The pain was measured before the sedation (baseline scores), and at 30 min, and 1, 2, 4, 6, 8, 12, 20 and 24 hours after extubation, using the Glasgow Composite Pain Scale (GCPS) 3,23 . Next, pain was assessed using a Visual Analogue Scale (VAS) in which, 0=no pain and 100=worst possible pain, manifested by vocalization, aggression, and refusal to allow the examination) [1][2][3][4][5] .…”
Section: This Study Was Approved By the Institutional Animalmentioning
confidence: 99%
“…Orthopedic surgery in dogs is commonly associated with moderate to severe postoperative pain and inflammation [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%